Identifikasi Keanekaragaman Tumbuhan Paku (Pteridophyta) di Kebun Ratu Kabupaten Jombang - Fitrotul Khasanah; Abdul Hafiedh Arifianto; Ospa Pea Yuanita Meishanti (MASALIQ, 2026)
Fern diversity (Pteridophyta) is an important component in maintaining ecosystem balance, but information regarding its presence and morphological characteristics in Kebun Ratu, Jombang Regency, remains limited. This study aimed to identify fern species in the Kebun Ratu area and describe the morphological characteristics of each species as a basis for providing scientific information to support conservation and the development of learning media based on local potential. The study employed a qualitative approach with an exploratory descriptive design through a field survey. Data were collected through observation, semi-structured interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data display, and conclusion drawing. The results identified three fern species, namely Nephrolepis sp., Adiantum caudatum, and Pteris sp. The three species exhibited differences in morphological characteristics in terms of leaf shape, stem type, and sorus arrangement and were found in moist, shaded habitats near watercourses. These findings indicate that Kebun Ratu has potential as a fern habitat, although the number of identified species was relatively limited. This study contributes local flora inventory data that can be used as a basis for conservation, the preparation of educational herbaria, and the development of environmentally based biology learning media.